Spectral Analysis of the Periodic Water Level Changes in the Baltic (Practical Application) - Laska, Mieczysław (The International Hydrographic Review, 2015)
This paper deals with the practical application of the autocorrelation and power spectrum methods to the analysis of periodic water level oscillations. A review of the theory and practical calculations of the periodic water level changes in the Baltic by means of autocorrelation and power spectrum methods is given. Both methods give the possibility to evaluate, from a superimposed series of data of different periods, that periodic component which is of greatest interest. This can be done by a series of smoothing operations, namely by a filtration which eliminates from the input data (e.g. mareogram) all unimportant additional periods. The general discussion of the theoretical basis o f the above-mentioned methods, and especially, the analysis of the water level oscillations at Sopot and Koiobrzeg (Polish coast - Southern Baltic) may provide a good tool for practical calculations to determine the periodic water level variations in various reservoirs.